Effect of surface loading pattern on the monosymmetric beams at elevated temperature. (2022) - Suman, Saurabh; Samanta, Avik
Abstract: Nowadays constructional steel has become the desired choice of structural designers because of its structural properties over other materials. However, structural steel susceptible to fire hazard as material properties of steel decreases rapidly at high temperatures that led to the instability failure of the unrestrained flexural members. In this study, numerical analysis is carried out to investigate the effect of surface loading patterns and temperatures on the buckling behavior of monosymmetric I-section beams. The ISMB600 monosymmetric beam of lengths varying from 2.5 m to 20 m simulated and analyzed using FEM based software ABAQUS. The response of beams is studied under uniform thermal conditions as well as transient thermal condition with 50% load ratio. Considerable variation in buckling capacity is noticed at elevated temperature. Based on the present results, the loading pattern is found to exhibit a significant influence on the moment capacities. The comparison between the numerical results and codal provisions of Eurocode 3 revealed that the codal provisions of Eurocode 3 pertaining to the buckling behavior of monosymmetric I-beams lead to the over-conservative prediction for medium to high slender beams and unsafe for beams having low slenderness ratio.